Actors and ideas behind CCTs in Chile, Costa Rica and El Salvador - Voorend, Koen (2011)
Conditional Cash Transfer programs are currently at a crossroads, between consolidating minimum safety nets and laying the basis for a universal system. In assessing which direction CCTs will take, it is important to analyze their formation. What domestic actors have been influential and how have expert-driven international ideas entered the domestic policy process? Is the impact related to existing welfare regimes? In this article the authors show that in general CCTs are the product of top-down and closed policy formation by elite coalitions, in which international factors play a central role. Nevertheless, domestic factors associated with welfare regimes, in particular the difference between state and non-state, informal regimes, account for important cross-national variations. If CCTs are to become a stepping-stone to universal social policy, closed policy communities have to be opened up.